COMPLEMENTARY AND ALTERNATIVE MEDICINE (CAM) ON DYSMENORRHEA: A SYSTEMATIC REVIEW - 1Nilam Noorma, 2Masni, 3 Andi Zulkifli, 4Andi Mardiah Tahir, (Chelonian Research Foundation, 2024)
Objectives: This systematic review aimed to evaluate the current evidence regarding the complementary alternative medicine on primary dysmenorrhea. Method: This systematic review study used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. The literature search was done using Google Scholar, Pubmed, and Science Direct. Articles that met the inclusion criteria were assessed using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) Checklist, including an explanation of sample size, explanation of sample methodology, calculation of response rate, findings/results measurement, explanation of the statistical analysis, confounding control, explanation of study limitations, and research ethics. Three independent reviewers participated in data extraction and assessment. Total of 20 out of 3,825 articles met the inclusion and exclusion criteria for review. Results: This review included 36 RCTs; the meta-analysis included 48 RCTs. Most studies showed a low or unclear risk of bias. The characteristic of the articles is the use of a clinical/controlled trial and quasi-experimental study design with the intervention target being the complementary alternative medicine on primary dysmenorrhea, the quality of the articles is categorized as good, and the measurement tools used are questionnaires and interviews. The cause of primary dysmenorrhea is often associated with high levels of inflammation in the endometrium. Elevated prostaglandin levels respond to the rise and fall of progesterone after ovulation. Overproduction of prostaglandins in the endometrium will result in hypercontractility and vasoconstriction of the myometrium. Vasoconstriction of the uterine blood vessels will reduce blood flow, muscle ischemia, and increase sensitivity to pain receptors, all of which cause period pain. Prostaglandin levels in adolescents with dysmenorrhea were twice as high as those without dysmenorrhea Conclusion: The results of this study suggest that acupuncture might reduce menstrual pain and associated symptoms more effectively compared with no treatment or NSAIDs, and the efficacy could be maintained during a short-term follow-up period. Keywords: complementary and alternative medicine; dysmenorrhea; students